The curious case of “trust” in the light of changing doctor–patient relationships - Segers, Seppe (Bioethics, 2022)
The centrality of trust in traditional doctor–patient relationships has been criticized as inordinately paternalistic, yet in today's discussions about medical ethics—mostly in response to disruptive innovation in healthcare—trust reappears as an asset to enable empowerment. To turn away from paternalistic trust-based doctor–patient relationships and to arrive at an empowerment-based medical model, increasing reference is made to the importance of nurturing trust in technologies that are supposed to bring that empowerment. In this article we stimulate discussion about why the move towards patient empowerment may not be able to keep clear of the criticism of trust in traditional patient–doctor relationships. First, we explore how such a shift in trust dynamics might corrode patient empowerment in the name of patient empowerment. Second, we examine how a translocation of trust may at best push the “trust issue” elsewhere and at worst make it harder to evaluate trustworthiness.